The phenomenon of spirituality in the Kazakh art songs - A. S., Sabirova; A. T., Yergalieva; A., Maulet; M., Gabdiyev; R., Takezhanova (Opción, 2020)
The given work presents the results of the analysis of the main traditions existing in Kazakh singing art. The article was written in the framework of the project “Study, preservation and popularization of the cultural heritage of Sary-Arka” (Project identifier: BR05236868). The purpose of this study is to shed light on the spiritual nature of the Kazakh folklore and art songs. The object of this study is Kazakh traditional song, since song is the foundation of the musical culture of each ethnic group. The revival of a song always coincides with the beginning of folk musical self-knowledge, folk self-consciousness.